An inflation-predicting measure of the output gap in the euro area - Marek Jarociński; Michele Lenza (European Central Bank (ECB), 2016)
Using a small Bayesian dynamic factor model of the euro area we estimate the deviations of output from its trend that are consistent with the behavior of inflation. We label these deviations the output gap. In order to pin-down the features of the model, we evaluate the accuracy of real-time inflation forecasts from different model specifications. The version that forecasts inflation best implies that after the 2011 sovereign debt crisis the output gap in the euro area has been much larger than the official estimates. Versions featuring a secular-stagnation-like slowdown in trend growth, and hence a small output gap after 2011, do not adequately capture the inflation developments.
Keywords: C32; C53; E31; E32; E37; 330; factor model; inflation forecast; output gap; Phillips curve